Banking governance, performance and risk-taking : conventional banks vs Islamic banks - Bouheni, Faten Ben; Ammi, Chantal; Levy, Aldo (London, UK : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2016)
Development of emerging countries is often enabled through non-conventional finance. Indeed, the prohibition of interest and some other impediments require understanding conventional finance and Islamic finance, which both seek to be ethical and socially responsible. Thus, comparing and understanding the features of Islamic banking and conventional banking, in a globalized economy, is fundamental. This book explains the features of both conventional and Islamic banking within the current international context. It also provides a comparative view of banking governance, performance and risk-taking of both finance systems. It will be of particular use to practitioners and researchers, as well as to organizations and companies who are interested in conventional and Islamic banking. Development of emerging countries is often enabled through non-conventional finance. Indeed, the prohibition of interest and some other impediments require understanding conventional finance and Islamic finance, which both seek to be ethical and socially responsible. Thus, comparing and understanding the features of Islamic banking and conventional banking, in a globalized economy, is fundamental. / /This book explains the features of both conventional and Islamic banking within the current international context. It also provides a comparative view of banking governance, performance and risk-taking of both finance systems. It will be of particular use to practitioners and researchers, as well as to organizations and companies who are interested in conventional and Islamic banking.
From Corporate Governance to Banking Governance -- From Corporate Governance to Banking Governance. Corporate Governance: A Brief Literature Review -- Banking Governance -- Islamic Banking Governance -- Mechanisms of Corporate Governance, Banking Governance and Islamic Banking Governance -- Banking Performance -- Banking Performance. Performance Measurement -- Corporate Governance and Performance -- Banking Risk-Taking -- Banking Risk-Taking. Banking Governance and Performance -- Banking Risk Analysis -- Banking Risk Management -- Corporate Governance and Risk-Taking.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed September 29, 2016).
Keywords: Banking law; Banking law (Islamic law); LAW / Administrative Law & Regulatory Practice; Banking law; Banking law (Islamic law); Electronic books